Towards a Connected Interpretation of Experience in the Philosophy of David Hume - Calvente, Sofía (ARFIL y UNL, 2022)
This paper aims at clarifying the meaning and function of experience within the framework of Hume's theory of knowledge. In order to do so, I will examine two interpretations that can be reconstructed in secondary literature: the one which understands experience as simple impressions of sensation and the one that conceives it as patterns of connected perceptions. I argue that the first perspective is not suitable to understand the epistemic role of the experience, which inclines me towards the second interpretation. However, this interpretation has not been sufficiently developed by the authors who suggest it. My purpose is to carry out this task, offering a series of clarifications that make it more robust in order to elucidate why, for Hume, experience is the touchstone concerning knowledge about matters of fact. Thus, I will show that the meaning of experience within causal inferences is related to cases that we collect through observation and arrange into collections or patterns, which work as evidence to establish or justify epistemic statements. Finally, in order to accurately understand its function within this type of inferences, I will distinguish experience from impressions and habit.